2-Year survival benefit from immunotherapy for squamous cell cancer with cancer of unknown primary in mediastinum: a case report - Zhao, Wei; Zhao, Nan; Zhang, Manze; Li, Zhihua; Wang, Ning; Shen, Wennan; Dong, Yuemei; Nie, Yanli; Li, Zhaoxia (Frontiers in Oncology, 2023)
Cancers of unknown primary (CUP) accounts for 2-5% of all diagnosed cancers, is always characterized with fast-paced aggression, early metastasis, and unpredictable spread patterns Mediastinum metastasis with unknown primary origin is extremely rare, as well as with a poor prognosis and short survival. There is no literature to refer to for its treatment. Here, we reported a cases of Squamous cell CUP in mediastinum. A 50-year-old male patient was admitted after multiline treatment of low differentiated squamous cell carcinoma in mediastinum diagnosed 8 months before. In August 2019, the patient went to local hospital for cough and dyspnea for 2 weeks. Then he was diagnosed with squamous cell carcinoma of unknown primary origin with multiple lymph nodes metastasis. The patient was featured with programmed cell death-ligand 1 (PD-L1) expression strongly positive in 90% of tumor cells and the combined positive score of 90 and a tumor mutation burden of 1.79 MUts/Mb and microsatellite stable phenotype. The patient was treated with antiprogrammed cell death-1(PD-1) antibodies in combination with chemotherapy and responded to the treatment. The patient showed stable disease to multi-line immunotherapy for more than 7 months and finally got a clinical benefit of 2-year survival benefit. In conclusive, immunotherapy targeting PD-1/PD-L1 in combination with chemotherapy may play a crucial role in the later-line treatment and palliative care of CUP.